Efektivitas Komisaris Independen dalam Memoderasi Pengaruh Karakteristik Direksi terhadap Manajemen Laba - Adila Pranoto Putri; Lia Uzliawati (Politeknik Ganesha Medan, 2026)
This study examines the effects of narcissistic directors and director tenure on earnings management, and investigates whether independent commissioners moderate these relationships. Using panel data from 39 basic materials firms listed on the Indonesia Stock Exchange during 2020–2024 (195 firm-year observations), this study employs panel regression analysis. The results show that narcissistic directors positively affect earnings management, whereas director tenure has no significant effect. The findings also reveal that independent commissioners weaken the positive effect of narcissistic directors on earnings management, but do not moderate the relationship between director tenure and earnings management. These results suggest that psychological characteristics of directors play a more prominent role in shaping earnings management than structural characteristics such as tenure. This study contributes to the Upper Echelons Theory literature by showing that the influence of top executives on financial reporting quality is contingent on governance effectiveness, particularly the monitoring role of independent commissioners. The findings provide practical implications for firms and regulators to strengthen board oversight, especially in monitoring executives with strong self-enhancement tendencies.